Problematic Aspects of Regional Development Policy in Bulgaria - Petrov, Kamen (UNWE Yearbook, 2021)
Bulgaria implements a socio-economic policy aimed at the development of an efficient and competitive economy and equitable integration in the European structures. The regional development policy, which is assuming importance, is part of this policy. The problems in the development of urban territories are particularly topical in the countries of Central and Eastern Europe due to the ongoing processes of transformation. The settlement structure forms the basis of the existence and interaction of society and thus offers geo-demographic characteristics of the territory. The problems of the urbanized systems are brought to the fore with increasing problems of the improvement and functioning of the individual settlements. These problems raise the need to systematize geographical theory through the prism of regional development and the development of intelligent urban management systems.
Keywords: Accession; Regional; Development; Integration; Processes; Urban; Territory